Die Werkstatt des Dichters. Imaginationsräume literarischer Produktion - Maurer, Stefan (Literatur und Archiv, 2017)
The "poet's workshop" is a central imaginary space of literature. What do we imagine when we think about the workspaces of major writers? Does it make sense to speak about the fantasia of the archive, analogous to how Michel Foucault spoke about the fantasia of the library of literature? What is the relationship between the imaginary spaces of writing and the real experience of modes of production?